Blood lead and cadmium levels associated with hematological and hepatic functions in patients from an e-waste-polluted area. (April 2019) - Chen, Yanrong; Xu, Xijin; Zeng, Zhijun; Lin, Xueqiong; Qin, Qilin; Huo, Xia
Abstract: Chronic exposures to toxic trace metals have hazardous effects on human health, especially exposure to lead (Pb) and cadmium (Cd). Blood Pb and Cd reflect toxicity on human health. A total of 267 hospitalized patients, of which 158 were from Guiyu (exposed group) in China, and 109 from Jinping (reference group), were recruited in this study. Blood Pb and Cd were measured by graphite furnace atomic absorption spectrometry. Blood Pb and Cd levels from the exposed group were both higher than in the reference group. Blood Pb levels are positively associated with blood Cd levels from the two groups. Blood Pb and Cd levels are associated with elevated hematological and hepatic parameters in patients from the exposed and reference groups. The results suggest toxic trace metals may increase liver metabolic burden, inducing abnormal liver function. Graphical abstract: Image 1 Highlights: Liver enzymes and red blood cells are affected by blood Pb and Cd. Toxic trace metals in blood reflect the burden of liver and red blood cells. Risk of abnormal liver function is linked with exposure of Pb and Cd. The exposed area is considered as the entry point to explore human liver health.